2016
DOI: 10.1002/uog.15661
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting the real-time dynamic ‘sliding sign’ and predicting pouch of Douglas obliteration: an interobserver, intraobserver, diagnostic-accuracy and learning-curve study

Abstract: Objective To determine inter-and intraobserver agreement, diagnostic accuracy and the learning curve required for interpreting the 'sliding sign' and predicting pouch of Douglas (POD) obliteration. Methods This was an inter-/intraobserver 65.4 to 96.2%, 80.0 to 100%, 64.7 to 100%, 50.0 to 100% and 94.7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 21 publications
1
42
2
Order By: Relevance
“…Although results from recent published data strengthen the clinical utilization of UBESS by demonstrating high reproducibility and acceptable interobserver agreement for phenotypes of higher‐stage endometriosis (e.g. bowel DIE and POD obliteration), it is important to evaluate appropriately the reproducibility and interobserver agreement of other components of UBESS in future studies, especially among observers with different levels of training. Finally, UBESS was developed and applied retrospectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although results from recent published data strengthen the clinical utilization of UBESS by demonstrating high reproducibility and acceptable interobserver agreement for phenotypes of higher‐stage endometriosis (e.g. bowel DIE and POD obliteration), it is important to evaluate appropriately the reproducibility and interobserver agreement of other components of UBESS in future studies, especially among observers with different levels of training. Finally, UBESS was developed and applied retrospectively.…”
Section: Discussionmentioning
confidence: 99%
“…found that non‐specialist operators who had carried out 200 or more prior gynecological US examinations performed better than did those with less prior experience (50 prior scans) in the interpretation of offline videos of the sliding sign. Furthermore, the reproducibility of the sliding sign is good. Our findings suggest that absence of the sliding sign is more important than is presence of KO, as the latter had very high specificity but very low sensitivity, while for the former both sensitivity and specificity were around 75%.…”
Section: Discussionmentioning
confidence: 55%
“…demonstrated that two less experienced operators (trainees) achieved competence in detecting POD obliteration by absent sliding sign after only 42 and 37 patients, respectively. Menakaya et al . found that non‐specialist operators who had carried out 200 or more prior gynecological US examinations performed better than did those with less prior experience (50 prior scans) in the interpretation of offline videos of the sliding sign.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations